MENINGKATKAN KREATIVITAS SENI MELALUI PELATIHAN MEMBUAT KARYA DENGAN MEMANFAATKAN BOTOL PLASTIK BEKAS - Cinthya, Anastasia; Kusuma, Heru Budi (Jurnal Pengabdian dan Kewirausahaan, 2018)
The background of the activity is to integrate the educational curriculum in the Interior Design Study Program, in this case is the Basic Design course, and the Creative Experiments course, with the National Curriculum program in elementary school. Training activities using used plastic bottle media and acrylic paints are training to make Nirmana Dwimatra or 2 dimensional Designs that utilize used goods. Activity Nirmana 2 Matra is application to design elements, ie point, line, plane, color, and texture which is processed by applying certain design principles, such as harmony (Harmony), Rhythm, repetition (Repetition), unity (Unity ), balance (balance), and other design principles. This training activity is intended to train and provide insight to children of primary school age, so that they can be inspired and able to innovate on the 2-dimensional works that they already know. Creativity and innovative work can be one way to generate motivation in conducting teaching and learning activities. Through the Community Service of the Faculty of Art and Design Tarumanagara University, lecturers can provide training to create 2-dimensional work, which in turn is expected to provide benefits to teachers and students to give birth to new works better and more innovative. 2-dimensional work processing skills are very useful in supporting teaching and learning activities tailored to the needs of the National Curriculum materials, such as the work of color composition and the work of processing the form. In addition, the 2 dimensional work of the results of the training, the work of teachers, and the expected work of the students, are displayed in the classroom so as to beautify the class and provide a new atmosphere in the arrangement of the classroom. Keywords : Nirmana dwimatra, creativity, curriculum.